Quantitative Wide-Field Imaging Techniques for Fluorescence Guided Neurosurgery - Valdes, Pablo A.; Juvekar, Parikshit; Agar, Nathalie Y. R.; Gioux, Sylvain; Golby, Alexandra J. (Frontiers in Surgery, 2019)
Fluorescence guided surgery (FGS) has fueled the development of novel technologies aimed at maximizing the utility of fluorescence imaging to help clinicians diagnose and in certain cases treat diseases across a breadth of disciplines such as dermatology, gynecology, oncology, ophthalmology, and neurosurgery. In neurosurgery, the goal of FGS technologies is to provide the neurosurgeon with additional information which can serve as a visual aid to better identify tumor tissue and associated margins. Yet, current clinical FGS technologies are qualitative in nature, limiting the ability to make accurate, reliable and repeatable measurements. To this end, developments in fluorescence quantification are needed to overcome current limitations of FGS. Here we present an overview of the recent developments in quantitative fluorescence guidance technologies and conclude with the most recent developments aimed at wide-field quantitative fluorescence imaging approaches in neurosurgery.